Professionalization of indigenous teachers. Challenges at the National Pedagogical University, Unit 071, Chiapas - Gómez, José Bastiani; López García, María Minerva (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2019)
The analysis of the teachers' formative process on indigenous education is necessary to revisit the notions of quality, equitable, and contextualized education. For this reason, we report in this paper the results of the research carried out at the Universidad Pedagógica Nacional, Unit 071, in Chiapas, Mexico. This research consisted of an ethnographic study that included the revision of the curricular structure and, in addition, the voice of teachers and students at different training scenarios was taken into account. According to the results, the curriculum is out-of-date and irrelevant to the needs of the target population. It was also found that it responds to an instrumental logic that profoundly affects teachers' formative process. The different languages of the original peoples are not promoted as a priority and their cosmovision is not recovered either. Based on these results, we reflect on the direction of indigenous teacher training.  There is an urgent need to rethink the curriculum from an intercultural perspective that gives value and strength to the identity of the communities of indigenous peoples.